2011
DOI: 10.1182/blood-2010-11-318949
|View full text |Cite
|
Sign up to set email alerts
|

Minimal cross-intolerance with nilotinib in patients with chronic myeloid leukemia in chronic or accelerated phase who are intolerant to imatinib

Abstract: Nilotinib has significant efficacy in patients with newly diagnosed chronic myeloid leukemia in chronic phase (CML-CP) and in patients with CML-CP or CML in accelerated phase (CML-AP) after imatinib failure. We investigated the occurrence of cross-intolerance to nilotinib in imatinib-intolerant patients with CML. Only 1/75 (1%) patients with nonhematologic imatinib intolerance experienced a similar grade 3/4 adverse event (AE), and 3/75 (4%) experienced a similar persistent grade 2 nonhematologic AE on nilotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 17 publications
2
38
0
2
Order By: Relevance
“…Importantly, the probability of crossintolerance across different TKIs is generally low. [20][21][22] This is particularly true for nonhematologic adverse events which occur infrequently, particularly at a grade 3 or 4 level, and rarely lead to treatment discontinuation for the same adverse event. In contrast, hematologic adverse events, particularly thrombocytopenia, are more likely to lead to cross-intolerance.…”
Section: Sequencing and Safetymentioning
confidence: 99%
“…Importantly, the probability of crossintolerance across different TKIs is generally low. [20][21][22] This is particularly true for nonhematologic adverse events which occur infrequently, particularly at a grade 3 or 4 level, and rarely lead to treatment discontinuation for the same adverse event. In contrast, hematologic adverse events, particularly thrombocytopenia, are more likely to lead to cross-intolerance.…”
Section: Sequencing and Safetymentioning
confidence: 99%
“…Only 7 of 40 (18%) patients with hematologic imatinib intolerance discontinued nilotinib, all due to grade 3/4 thrombocytopenia. 18 In a dasatinib trial in patients with CP-CML, 6 of 46 (13%) patients had hematological cross-intolerance on dasatinib 100 mg once daily and subsequently discontinued dasatinib. 19 However, nonhematological crossintolerance to imatinib was uncommon with both nilotinib (2 of 109; 2%) and dasatinib 100 mg once daily (9 of 225; 4%).…”
Section: Management Of Treatment-related Adverse Effectsmentioning
confidence: 99%
“…One hundred patients were enrolled between 2007 and 2009; 69 patients had at least 12 months of follow-up (median, 24 months; range, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and 42 (61%) of these 69 patients relapsed (40 before 6 months, 1 patient at month 7, and 1 at month 19). At 12 months, the probability of persistent molecular remission for these 69 patients was 41%.…”
Section: Discontinuation Of Therapymentioning
confidence: 99%
“…Cortes et al previously reported that cross-intolerance to nilotinib in imatinib-intolerant patients with CML is infrequent, particularly for patients with nonhematologic adverse events, which is the most common reason for imatinib intolerance (22). This minimal crossintolerance resulted in more patients achieving the planned nilotinib doses and translated into significant clinical responses.…”
Section: Discussionmentioning
confidence: 99%